Crystal Guava-Based Agribusiness Development Strategy in Pelaga Village, Petang District - I Gusti Bagus Udayana; Yohanes Parlindungan Situmeang; Komang Nita Wedaningsih; Ni Made Ayu Suardani Singapurwa; I Gusti Agus Maha Putra Sanjaya; Ni Made Ayu Gemuh Rasa Astiti (Agriwar Journal, 2024)
Crystal guava is an attractive crop for cultivation in Indonesia. The limited expansion of the consumer market for fresh guava fruit is influenced by the quality of the fruit and the low shelf life of the fruit. Improvement of guava fruit quality is carried out to produce fruits that have a uniform shape, good size, and attractive fruit skin color. This study aims to analyze the effectiveness of the application of good and correct cultivation in increasing the productivity of crystal guava in Pelaga Village. The research method used is a case study with qualitative and quantitative approaches. Data were obtained through observation, interviews, and documentation. The results of the analysis show that the application of good and proper cultivation has a positive effect on increasing the productivity of crystal guava. In addition, the five highest factors in internal and external factors that affect crystal guava productivity were identified. IFE and EFE analysis on the IE Matrix showed that Pelaga Village has a strong position and opportunity, so seven strategies were developed to effectively increase the productivity and marketing of crystal guava. In conclusion, the application of good and correct cultivation is very important in increasing the productivity of crystal guava, and the strategies developed can be a guide for business development in the sector.